Pengendalian Pemanfaatan Ruang Kawasan Terdampak Banjir Di Perkotaan Sinjai - Muhammad Muhammad Afandi Naser; Murshal Manaf; Tri Budiharto (Fakultas Teknik Universitas Bosowa, 2021)
Abstract. This study aims to explain the characteristics of flood-affected areas, in order to analyze land suitability and spatial use in flood-affected areas and to formulate the concept of controlling the spatial use of flood-affected areas. This research is qualitative-quantitative with the analysis techniques used are scoring analysis, superimpose analysis, qualitative descriptive analysis and space envelope analysis. The results show that there are three classifications of flood hazard, namely low, medium and high, where in the high flood-prone areas in Sinjai city there are five villages, namely Balangnipa Village, Biringere Village, Bongki Village, Lappa Village and Samataring Village. The results of the second research objective were obtained from the overlay prone to flooding and the spatial pattern of the Sinjai urban RDTR, where the dominant spatial pattern of high flood prone areas is in the housing zone which covers an area of ​​564,185 hectares. The direction of the strategic concept based on three classifications of flood hazard in Sinjai urban areas is proposed in the form of disaster mitigation in the form of recommendations for flood control in accordance with the characteristics of flood-prone areas, and in controlling spatial use in the form of zoning regulations and permit proposals at the research location granting land use permits for each area prone to high, medium and low flood disasters. Abstrak. Penelitian ini bertujuan untuk menerangkan karakteristik kawasan terdampak banjir, guna menganalisis kesesuaian lahan dan pemanfaatan ruang pada kawasan terdampak banjir dan merumuskan konsep pengendalian pemanfaatan ruang kawasan terdampak banjir. Penelitian ini bersifat kualitatif-kuantitatif dengan teknik analisis yang digunakan adalah analisis skoring, analisis superimpose, analisis deskriptif kualitatif dan analisis amplop ruang. Hasil penelitian diketahui bahwa terdapat tiga klasifikasi kerawanan banjir yaitu rendah, sedang dan tinggi yang dimana pada kawasan rawan banjir tinggi di perkotaan Sinjai terdapat di lima kelurahan yaitu Kelurahan Balangnipa, Kelurahan Biringere, Kelurahan Bongki, Kelurahan Lappa dan Kelurahan Samataring. Adapun hasil tujuan penelitian kedua yang didapat dari overlaynya rawan banjir dan pola ruang RDTR perkotaan Sinjai, dimana yang berdominan pada pola ruang kawasan rawan banjir tinggi terdapat di zona perumahan yang luasnya sebesar 564.185 Ha. Arahan konsep strategi berasarkan tiga klasifikasi kerawanan banjir di kawasan perkotaan Sinjai diusulkan dalam bentuk mitigasi bencana berupa rekomendasi pengendalian banjir yang sesuai dengan karakteristik pada kawasan rawan banjir, dan pada pengendalian pemafaatan ruang berupa peraturan zonasi dan usulan perizinan di lokasi penelitian dapat disimpulkan bahwa terdapat perbedaan perilaku pemberian perizinan penggunaan lahan pada setiap kawasan rawan bencana banjir tinggi, sedang maupun rendah.